The Effectiveness of Utilising the Building Information Modelling Based Tools for Safety Training and Job Hazard ?dentification - Darda’u Rafindadi, Aminu; Shafiq, Nasir; Othman, Idris; Aliyu, M. M.; Alarifi, Hamzh; Ibrahim, Ahmad; Aliyu Yaro, Nura Shehu (Journal of Technology Management and Business, 2023)
The fields of architecture, engineering and construction (AEC) have kept pace with recent technological developments in design and construction. However, it is difficult to obtain information on the breadth of applications of BIM -based tools throughout the life cycle of construction projects. Hence, this study attempts to empirically identify and evaluate the applications of pre-construction tools, with a focus on safety training and workplace hazard recognition. A questionnaire in the form of a survey was used to collect data. The results show that the ten predictors account for 52.3% of the variation in BIM knowledge (F (10, 56) = 6.133, p < 0.001). It is also found that site analysis and safety instructions have no effect on the measured variable. The study represented a comprehensive blend of research to improve the use of BIM -based tools for safety training and workplace hazard identification. It also contributed to the knowledge of how to use BIM -based tools in the pre-construction phase. The development of the BIM -process flow framework for safety training and hazard identification will be the main focus of future work.